2020
DOI: 10.1021/acs.nanolett.9b04579
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Inside Carbon Nanoreactors for Selective Allylic Oxidation of Cyclohexene

Abstract: The confinement of cerium oxide nanoparticles within hollow carbon nanostructures has been achieved and harnessed to control the oxidation of cyclohexene. Graphitised carbon nanofibres (GNF) have been used as the nanoscale tubular host and filled by sublimation of the Ce(tmhd)4 complex (where tmhd = tetrakis(2,2,6,6-tetramethyl-3,5-heptanedionato)) into the internal cavity, followed by a subsequent thermal decomposition to yield the hybrid nanostructure CeO2@GNF, where nanoparticles are preferentially immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 81 publications
2
40
0
Order By: Relevance
“…Among the studied samples, CuO FL2 shows the highest catalytic activity in terms of the conversion of cyclohexene with high selectivity towards 2‐cyclohexen‐1‐one, which is ascribed to its high surface charge and active exposed facet. It is worth mentioning that the CuO FL2 exhibits a comparable cyclohexene conversion and a higher 2‐cyclohexen‐1‐one selectivity than that reported recently with CeO 2 @graphifitized carbon nanofibers [51] . A more detailed comparison on the cyclohexene conversion and 2‐cyclohexen‐1‐one selectivity in presence of different catalysts is outlined in Table S1, which clearly establishes the advantages of the present catalyst.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Among the studied samples, CuO FL2 shows the highest catalytic activity in terms of the conversion of cyclohexene with high selectivity towards 2‐cyclohexen‐1‐one, which is ascribed to its high surface charge and active exposed facet. It is worth mentioning that the CuO FL2 exhibits a comparable cyclohexene conversion and a higher 2‐cyclohexen‐1‐one selectivity than that reported recently with CeO 2 @graphifitized carbon nanofibers [51] . A more detailed comparison on the cyclohexene conversion and 2‐cyclohexen‐1‐one selectivity in presence of different catalysts is outlined in Table S1, which clearly establishes the advantages of the present catalyst.…”
Section: Resultssupporting
confidence: 72%
“…It is worth mentioning that the CuO FL2 exhibits a comparable cyclohexene conversion and a higher 2-cyclohexen-1-one selectivity than that reported recently with CeO 2 @graphifitized carbon nanofibers. [51] A more detailed comparison on the cyclohexene conversion and 2-cyclohexen-1-one selectivity in presence of different catalysts is outlined in Table S1, which clearly establishes the advantages of the present catalyst. It is interesting to find that despite of having a similar chemical composition and higher surface area in CuO PLs compared to CuO FLs, the catalytic activity is better in the case of CuO FLs.…”
Section: Catalytic Activity Of the As-synthesized Cuomentioning
confidence: 60%
See 1 more Smart Citation
“…Besides that, due to their wide range of pharmacological action, they may be used for the creation of new drugs [205,206] and also as reagents in fine organic synthesis [207][208][209][210][211]. All this makes it relevant to consider the conformational properties of these compounds inside nanotubes, from the perspectives of nanoreactors [68][69][70][71][72][73][74][75] and drug delivery systems [15,19].…”
Section: 3-dioxane In Nanotubesmentioning
confidence: 99%
“…On the other hand, the calculated energy barrier for Cl − exchange in the S N 2 reaction within nanotubes was higher by 6.6 kcal/mol in comparison with the gas phase [69]. Later, it was shown that SWCNTs may be used as effective nanoreactors for preparative syntheses of inorganic [70] and organic [71][72][73][74][75] products with high yields; it is also possible to achieve enantiomeric excess of the products by using a racemic mixture of P and M enantiomers of (n,m) chiral nanotubes [76].…”
Section: Introductionmentioning
confidence: 99%